Xq26.3 Duplication in a Boy With Motor Delay and Low Muscle Tone Refines the X-Linked Acrogigantism Genetic Locus. - Trivellin, Giampaolo; Sharwood, Erin; Hijazi, Hadia; Carvalho, Claudia M B; Yuan, Bo; Tatton-Brown, Katrina; Coman, David; Lupski, James R; Cotterill, Andrew M; Lodish, Maya B; Stratakis, Constantine A (J Endocr Soc, 2018)
We describe a 4-year-old boy with developmental delay who was found to carry by clinical grade (CG) molecular cytogenetics (MCs) a chromosome Xq26 microduplication. The report prompted a referral of the patient for possible X-linked acrogigantism (X-LAG), a well-defined condition (MIM300942) due to chromosomal microduplication of a nearby region. The patient was evaluated clinically and investigated for endocrine abnormalities related to X-LAG and not only did he not have acrogigantism, but his growth parameters and other hormones were all normal. We then performed high definition MCs and the duplication copy number variant (CNV) was confirmed to precisely map outside the X-LAG critical region and definitely did not harbor the X-LAG candidate gene, . The patient's phenotype resembled that of other patients with Xq26 CNVs. The case is instructive for the need for high definition MCs when CG MCs' results are inconsistent with the patient's phenotype. It is also useful for further supporting the contention that is the gene responsible for X-LAG.